PENGEMBANGAN MEDIA QUIET BOOK BERBASIS MULTIMODAL UNTUK NUMERASI SISWA KELAS I SEKOLAH DASAR - Dewi Apriliani Yusuf; Siti Raihan; Samsuriyani Eka Putri Atjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low numeracy skills of first-grade elementary school students, particularly in basic addition and subtraction operations, due to the lack of interactive and concrete learning media. This study aims to develop a Multi-modal-based Quiet Book as a learning medium for number concepts that is valid, practical, and effective. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were first-grade students at SD Inpres Panaikang II/1. Data collection techniques included observation, interviews, and questionnaires. The results showed that the Multi-modal Quiet Book was declared